The first shall be last: serial position effects in the case contestants evaluate each other - Stefan D. Haigner; Stefan Jenewein; Hans-Christian Müller; Florian Wakolbinger (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2010)
We analyze competitions where the contestants evaluate each other and find the first contestant to be disadvantaged. We suspect that this is due to information diffusion, Bayesian belief updating taking place in course of the contest and initial uncertainty about a contestant's relative quality.
Keywords: C12; D81; 330; Serial Position Effects; Ordering Effects; Wettbewerb; Potenzieller Wettbewerb; Entscheidung bei Unsicherheit; Theorie